Heavy mechanical force decelerates orthodontic tooth movement via Piezo1-induced mitochondrial calcium down-regulation - Ye Zhu; Xuehuan Meng; Qiming Zhai; Liangjing Xin; Hao Tan; Xinyi He; Xiang Li; Guoyin Yang; Jinlin Song; Leilei Zheng (Genes and Diseases)
Orthodontic tooth movement (OTM) depends on periodontal ligament cells (PDLCs), which sense biomechanical stimuli and initiate alveolar bone remodeling. Light (optimal) forces accelerate OTM, whereas heavy forces decelerate it. However, the mechanisms by which PDLCs sense biomechanical stimuli and affect osteoclastic activities under different mechanical forces (MFs) remain unclear. This study demonstrates that mechanosensitive ion channel Piezo1-mediated Ca2+ signal conversion is crucial for sensing and delivering biomechanical signals in PDLCs under heavy-force conditions. Heavy MF up-regulated Piezo1 in PDLCs, reducing mitochondrial Ca2+ influx by inhibiting ITPR3 expression in mitochondria-associated membranes. Decreased mitochondrial calcium uptake led to reduced cytoplasmic release of mitochondrial DNA and inhibited the activation of the cGAS‒STING signaling cascade, subsequently inhibiting monocyte-to-osteoclast differentiation. Inhibition of Piezo1 or up-regulation of STING expression under heavy MF conditions significantly increased osteoclast activity and accelerated OTM. These findings suggest that heavy MF-induced Piezo1 expression in PDLCs is closely related to the control of osteoclast activity during OTM and plays an essential role in alveolar bone remodeling. This mechanism may be a potential therapeutic target for accelerating OTM.